DISASTER VICTIM MANAGEMENT Palu City, Celebes Island Earthquake – September, 28th 2018 - Franky Franky; Thomas Budiman (AIBPM Publisher, 2019)
This paper aims to create and deliver a guidance to Government through related agencies in helping all disaster victims, especially those victims of tsunami disaster that hit Palu city on September 2018. The guidance created based on demography and fear level experienced by the victims. No one can predict where and when the natural disaster will take place (force majure). By not knowing the exact time and place of the disaster, the effect resulted of this disaster is inavoidable. The central and local government are expected to have a standard operation procedures (SOP) to handle all of the victims, to minimize the secondary effect caused. The secondary effect that may arise because of the lateness delivery of support may get the impact even worst like destruction of houses, grieves of being left alone, long-drawn traumatic and fear. The government is expected to have the best management tool to help them by their demographic condition and other factors that caused fear and traumatic. The method used in this paper is by spreading questionaire and conducting interview to at least 128 victim population who are above 20 years of age. The sample taken by purposive sampling method one month after the disaster occurred. Data analysis method done using frequency table and contingency table. As the result of this paper aims to assist government both local and central and their related agencies to distribute aid targeted, comprehensive and systematically.